Analysis of corporate integrity practices: evidence from Malaysian companies - Abdul Jabar, Ja’izah; Kasim, Eley Suzana; Md Zin, Norlaila; Ismail, Norhidayah; Dol @ Abdul Wahid, Akma Hidayu; Abdul Razak, Rafizan (2022)
The recent rise in corruption and other integrity concerns has prompted the Malaysian government's interest in developing a good integrity evaluation instrument. Malaysian Institute of Integrity (IIM) together with a group of researchers introduced Integrity Assessment Tool (IAT) Self-Assessment Questionnaire in 2010. This tool was designed to systematically measure and evaluate the process of incorporating integrity and ethics in the workplace. Thus, using the same assessment questionnaire, this study will analyse the practice of corporate integrity in the selected Malaysian companies. This study employed content analysis to examine the prominent practices embraced by fourteen selected Malaysian companies. Based on the analysis, it was found that the top three practices are legal compliance, vision and ethical communications. This finding could help anti-corruption institutions and management to develop better strategies to incorporate and evaluate integrity and ethics.